Financial Cooperatives in Haiti : A Diagnostic Review of the Sector and its Regulatory and Supervisory Framework - Funke, Ilka; World Bank Group (World Bank, Washington, DC, 2020)
The government and the Central Bank of Haiti (BRH) aim to improve financial inclusion to foster more inclusive economic growth. With the support of the World Bank, the government developed a national financial inclusion strategy in 2014. Since financial cooperatives play an important role for financial inclusion, the strategy calls for an assessment of constraints to their development, as well as the development of an action plan to strengthen and consolidate the sector. This diagnostic report aims to provide this assessment of the sector. It also offers recommendations for reforms that should be incorporated into a sector wide action plan.